Ginkgolide B inhibits the neurotoxicity of prions or amyloid-β(1-42) - Bate, Clive (BioMed Central, 2004)
BACKGROUND: Neuronal loss in Alzheimer's or prion diseases is preceded by the accumulation of fibrillar aggregates of toxic proteins (amyloid-β(1-42 )or the prion protein). Since some epidemiological studies have demonstrated that the EGb 761 extract, from the leaves of the Ginkgo biloba tree, has a beneficial effect on Alzheimer's disease, the effect of some of the major components of the EGb 761 extract on neuronal responses to amyloid-β(1-42), or to a synthetic miniprion (sPrP106), were investigated. METHODS: Components of the EGb 761 extract were tested in 2 models of neurodegeneration. SH-SY5Y neuroblastoma cells were pre-treated with ginkgolides A or B, quercetin or myricetin, and incubated with amyloid-β(1-42), sPrP106, or other neurotoxins. After 24 hours neuronal survival and the production of prostaglandin E(2 )that is closely associated with neuronal death was measured. In primary cortical neurons apoptosis (caspase-3) in response to amyloid-β(1-42 )or sPrP106 was measured, and in co-cultures the effects of the ginkgolides on the killing of amyloid-β(1-42 )or sPrP106 damaged neurons by microglia was tested. RESULTS: Neurons treated with ginkgolides A or B were resistant to amyloid-β(1-42 )or sPrP106. Ginkgolide-treated cells were also resistant to platelet activating factor or arachidonic acid, but remained susceptible to hydrogen peroxide or staurosporine. The ginkgolides reduced the production of prostaglandin E(2 )in response to amyloid-β(1-42 )or sPrP106. In primary cortical neurons, the ginkgolides reduced caspase-3 responses to amyloid-β(1-42 )or sPrP106, and in co-culture studies the ginkgolides reduced the killing of amyloid-β(1-42 )or sPrP106 damaged neurons by microglia. CONCLUSION: Nanomolar concentrations of the ginkgolides protect neurons against the otherwise toxic effects of amyloid-β(1-42 )or sPrP106. The ginkgolides also prevented the neurotoxicity of platelet activating factor and reduced the production of prostaglandin E(2 )in response to platelet activating factor, amyloid-β(1-42 )or sPrP106. These results are compatible with prior reports that ginkgolides inhibit platelet-activating factor, and that platelet-activating factor antagonists block the toxicity of amyloid-β(1-42 )or sPrP106. The results presented here suggest that platelet-activating factor antagonists such as the ginkgolides may be relevant treatments for prion or Alzheimer's diseases.